PENGARUH KONSENTRASI DAN TEKNIK PEMBERIAN KOLKHISIN TERHADAP PERTUMBUHAN VEGETATIF PADA BAWANG PUTIH (Allium sativum L) THE EFFECT OF COLCHICIN CONCENTRATION AND APPLICATION TECHNIQUE ON VEGETATIVE GROWTH OF GARLIC (Allium sativum L.) - Putrasamedja, Sartono (Pembangunan Pedesaan, 2005)
Research aimed at finding out good concentration of colchicin applied to the vegetative growth on garlic (Allium sativum L). The research was conducted at Balitsa experiment Garden from October 2002 until June 2003. A factorial Randomized Block Design with four replications was used. Treatment of colchicin with concentration was 250 (k ), 375 (k ), and 500 ppm (k ), and application 1 2 3 treatment were dripped to basal plate (t ), dripped to diagonal position of bulb (t ), 1 2 dipped for 6 hours (t ). The result showed that: (1) Dripped application of 375 ppm 3 colchicin at the plate and concentration of 500 ppm to sprinkle on diagonal cross gave positive effect on plant growth, (2) Dipped application of 250 ppm colchicin affected plant height at 6 week after planting; (3) Colchicin application of 375 ppm with sprinkle at basal plate was the best effect on foliar length at 7 week after planting.